Advancement of the 5-Amino-1-(Carbamoylmethyl)-1H-1,2,3-Triazole-4-Carboxamide Scaffold to Disarm the Bacterial SOS Response - Selwood, Trevor; Larsen, Brian J.; Mo, Charlie Y.; Culyba, Matthew J.; Hostetler, Zachary M.; Kohli, Rahul M.; Reitz, Allen B.; Baugh, Simon D. P. (Frontiers in Microbiology, 2018)
Many antibiotics, either directly or indirectly, cause DNA damage thereby activating the bacterial DNA damage (SOS) response. SOS activation results in expression of genes involved in DNA repair and mutagenesis, and the regulation of the SOS response relies on two key proteins, LexA and RecA. Genetic studies have indicated that inactivating the regulatory proteins of this response sensitizes bacteria to antibiotics and slows the appearance of resistance. However, advancement of small molecule inhibitors of the SOS response has lagged, despite their clear promise in addressing the threat of antibiotic resistance. Previously, we had addressed this deficit by performing a high throughput screen of ~1.8 million compounds that monitored for inhibition of RecA-mediated auto-proteolysis of Escherichia coli LexA, the reaction that initiates the SOS response. In this report, the refinement of the 5-amino-1-(carbamoylmethyl)-1H-1,2,3-triazole-4-carboxamide scaffold identified in the screen is detailed. After development of a modular synthesis, a survey of key activity determinants led to the identification of an analog with improved potency and increased breadth, targeting auto-proteolysis of LexA from both E. coli and Pseudomonas aeruginosa. Comparison of the structure of this compound to those of others in the series suggests structural features that may be required for activity and cross-species breadth. In addition, the feasibility of small molecule modulation of the SOS response was demonstrated in vivo by the suppression of the appearance of resistance. These structure activity relationships thus represent an important step towards producing Drugs that Inhibit SOS Activation to Repress Mechanisms Enabling Resistance (DISARMER).